PENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA ANAK (5-6) MELALUI KEGIATAN PENDAMPINGAN PARENTING - Elih Solihatulmillah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
This study generally aims to obtain information and data on the reading ability of beginners to read early childhood 5-6. This research is a classroom action Research conducted at KOBER PAUD As.Syifa having the address at Jalan. Btn. Junti Asri Blok C.2. No. 2 villages. Junti District Jawilan, Banten District. The data collection technique is a reading ability for beginners of early childhood 5-6. The results showed that 1) there was an increase in the ability to read beginners early childhood 5-6 with parenting assistance; 2) parenting facilitation activities include mothers holding together with the teacher motivating children in the learning process.